منهج القرآن الكريم في التحذير من الجاهلية - عبدالله، عودة عبد عودة; سليم، بلال عبدالرحمن (جامعة العلوم الإسلامية العالمية - عمادة البحث العلمي, 2017)
يقوم هذا البحث على دراسة منهج القرآن الكريم في التحذير من الجاهلية. وقد ظهر هذا المنهج واضحا جليا من خلال تحذير القرآن الكريم من سلوك الجاهلية وبيان زيفها وبطلانها. ثم دعوة القرآن الكريم للإعراض عن الجاهلية، والنهي عن التشبه بها. إضافة لوصف الأمم الكافرة بالجهل، كما كان الحال مع قوم نوح عليه السلام وقوم عاد، وبني إسرائيل. وأخيرا بيان براءة الأنبياء عليهم السلام من الجهل والجاهلية، باعتبارها عنوانا للنكوص عن الحق والانحراف عن المنهج السليم. This research aims to investigate the Holy Quran’s approach regarding warning from Al-Jaheliyah (Non-Islamism). This approach has been clearly demonstrated by the Quran's warning of the unbelievers' behavior in Al-Jaheliyah (Non-Islamism) and its falsification and invalidity. Further, the Holy Quran calls for keeping away from Al- Jaheliyah and not imitating it. Furthermore, the paper describes pagan peoples with Al-Jaheliyah, as was the case with the people of Noah, Add people (the people of the Prophet Hud), and the people of Israel. Finally, the study clarifies the virtuousness of the prophets, peace be upon them, from ignorance and Al-Jaheliyah which is considered as a deviation from the right approach.
Keywords: التفسيرات الموضوعية -- القرآن الكريم -- المناهج القرآنية